Framing Analysis Media Kompas.com and Pikiran Rakyat.com: Cikampek Toll Road Accident Kilometers 58 - Gunawan, Nur Anggraeni; Putri, Shinta Hartini; Febyola, Helena (Yayasan Sinergi Kawula Muda, 2023)
The news about the Cikampek kilometers 58 Toll Road accident during the peak of Lebaran 2024 attracted a lot of public attention and was reported by various online media including by Kompas.com and Pikiran Rakyat.com. News about the Cikampek kilometers 58 toll road accident in these two media is important to study because these two media have the ability to frame the facts of an event based on different perspectives on the same event. The purpose of this study is to explain the construction of online media kompas.com and pikiran rakyat.com in framing events regarding the accident case that occurred at kilometers 58 Jakarta-Cikampek Toll Road. This research uses the Entman model framing analysis approach. The results of this study show that the two media have differences in the focus of content and narrative with the results of the analysis kompas.com constructed the news by exploring the cornology of the accident from the side of the Bus Driver's story. While the people's mind frames the news with a narrative that is built to touch the humanity of the Bus Driver's story and the response of netizens in responding to accident news.